2012
DOI: 10.2320/matertrans.maw201201
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Shunting Current at Cracked Part to Critical Current and <i>n</i>-Value in Multifilamentary Bi2223 Composite Tape

Abstract: Relation of transport current and n-value to collective crack-induced current shunting in BSCCO (Bi2223) multi-filamentary composite tape pulled in tension was studied experimentally and analytically. For analysis, the partial crack-current shunting model of Fang et al. was used by placing the collective crack as the partial one. It was shown that (a) collective crack-induced shunting current increases with increasing current (and voltage) and with increasing collective crack size, (b) the transport current no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(38 citation statements)
references
References 10 publications
(28 reference statements)
1
37
0
Order By: Relevance
“…It has been shown that the experimental results of coated-and filamentaryconductors are described well by this replacement. 5,6,14) Based on this finding, we use the single equivalent crack model for analysis also in this work.…”
Section: Measured Critical Currents (I C ) and N-valuesmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that the experimental results of coated-and filamentaryconductors are described well by this replacement. 5,6,14) Based on this finding, we use the single equivalent crack model for analysis also in this work.…”
Section: Measured Critical Currents (I C ) and N-valuesmentioning
confidence: 99%
“…(1) and (2), we can obtain the values of ð1 À fÞðL=sÞ 1=n 0 and R t by curve fitting to the measured VI curve, and, once they are estimated, the SmBCO ligament part-transported current I Sm and shunting current I s can be obtained, as has been shown in our preceding work. 5,6,14) In calculation with eqs. (1) and (2), the values of I c and n at · T = 497 MPa just below the onset stress of cracking were used as I c0 and n 0 (I c0 = 180, 171 and 183 A, and n 0 = 35.2, 36.1 and 32.2 for S1, S2 and S3, respectively).…”
Section: Model For Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…We use the model reported by Fang et al, 12) which treats crack-induced changes in V-I curves. We have used this model to analyze the V-I curve and estimate the I c and n-value in cracked DyBCO-and SmBCO-coated conductors, 4,5,811) and in Bi 2 Sr 2 Ca 2 Cu 3 O 10+x (BSCCO) filamentary conductors 22) containing collective cracks that are composed of successively fractured filaments in a transverse cross-section. 18,22) We showed that the experimentally measured V-I curves, I c , and n-value are described by this model.…”
Section: Introductionmentioning
confidence: 99%